Role of undergraduate teaching: a link between patients and program implementation - P. Priya, Karpaga; Raj, Utsav; Giri, Anjan Kumar (International Journal Of Community Medicine And Public Health, 2020)
In India, tuberculosis (TB) remains to be one of the communicable diseases of major public health concern. Majority of the vulnerable population remain in urban parts of India. The role of active case finding and notification takes a spotlight for the successful implementation of the program. This article gives a case report of how an undergraduate training in conducting a house-house field survey as a part of community postings have enabled a TB patient from getting a timely diagnosis and treatment follow up. The stigma associated with the disease still continues, which has been appropriately addressed by our urban health training center. This has enabled the patient to complete the treatment successfully and become a TB champion. This case report depicts the importance of community-based field training to undergraduate medical students to enhance their skills and ability as well as to strengthen the ongoing national programs, a blessing in disguise.